Pengembangan Kompetensi Pedagogik Menuju Sekolah Bermutu - Khusnan Khusnan; Budi Sutrisno (Jurnal VARIDIKA, 2014)
The purpose of this study was to determine the development paedagogical com petence to school quality at SDN Banaran 1 described in two subfocuses, namely: 1) Assess the characteristics of the development of curriculum related to the subject matter teachers, 2) Assessing the educational characteristics of the learning organization. Data were col lected through interviews (indepth interviews), observation and document. Data analysis was carried out in the field before and during the field with Miles and Hubberman models interactively through a process of data reduction, data display and conclusion drawing. Results and discussion concluded that the profiles of development paedagogical competence toward school quality at SDN Banaran 1 is the development of theories that exist in previous studies. The development of the theory can be aware of the characteristics of development paedagogical competence performed SDN Banaran 1 as: placing the school commit tee and education experts as partners, to establish communication with parents / guardians, provide training to teachers in selecting appropriate learning strategies and to develop learning materials, as well as reducing the burden of additional teachers. Moreover, in implementing educational learning, SDN Banaran 1 provides enrichment and improvement as well as the addition of the grade six class hours in particular, carry out learning inter action optimally position the child as a subject of learning, contextual learning materials, learning through small group and the maximum using facility to stimulate student learning.